Pengaruh Orang Tua, Keluarga, dan Lingkungan Sosial terhadap Perilaku Merokok Remaja - Hidayati, Nurul; Arianto, Dwini (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
The high prevalence of teenage smoking in Indonesia is a serious problem. This study aims to analyze the influence of the smoking behavior of close individuals to teenagers, including parents, family, and social environment, on the smoking behavior of teenagers in Indonesia. Using the National Socioeconomic Survey (SUSENAS) 2021 Data, with a sample of 187,277 adolescent individuals. The results of this study indicate that the smoking behavior of parents, family, and a smoking environment has a significant positive influence on teenage smoking behavior. Parents who smoke increase the likelihood of teenagers smoking by 1.61 times, while smoking family members also contribute to an increased likelihood by 1.57 times. The smoking environment has a relatively smaller influence with an increase of 1.11 times. Other factors such as age, gender, and adolescent school participation also have a significant influence on teenage smoking behavior, with males having a much higher likelihood of smoking compared to females. These findings provide important insights into the role of close individuals in shaping teenage smoking behavior and underscore the importance of adolescent smoking prevention efforts in Indonesia